The State of a Customer-Focused Library Service for Rajabhat University - Salee, Sonthaya; Hanpol, Tassana; Phisalpong, Kwanchadil (2017)
Library service for Customer-focused has become a keyword in this era because the customers have choices in seeking information or services that responds to a variety of needs. Therefore, the library has to revise its service by focusing on the customers in order to build the relationship between the library and the customers studying their behavior and needs as well as good relationships between librarians and the customers. Then, the derived information is readjusted, to seek for the opportunity for excellent service provision. Rajabhat Universities are a local university which provides on education, supports academic and advanced career opportunities, research, society service, transfers knowledge and technology, and preserves the arts and culture and community services. Additionally the library plays an important role in supporting, such as, mission for the success in objectives and goals of the Rajabhat University. The objective of this dissertation was to study the state of customer-focused library service for Rajabhat Universities, using qualitative research method. The samples were directors of the library, head of department library service who was the librarians from 8 Rajabhat Universities. The research results was found: mission vision strategy and policy of customer-focused library service for Rajabhat Universities and factors that support the development of customer-focused in library service. The results of this study is illustrated from the development model of a customer-focused library service appropriate a new paradigm of library in 21st Century.